Application of Debate Learning Method as An Effort To Improve Communication Skills In Civic Education Courses - S. Djirlay, Mariana; Murdiono, Mukhamad (Devotion : Journal of Research and Community Service, 2024)
This study aims to examine the effectiveness of the debate learning method in improving students' communication skills in the Civic Education course. The research method used is a case study with a qualitative approach, including observation, interviews, and analysis of assignment documents. The results of the study show that the application of the debate method significantly improves students' communication skills, especially in terms of expressing opinions logically and in a structured manner, listening to and responding to opponents' arguments well, and actively participating in the learning process. Therefore, the debate method can be an effective learning alternative in honing communication skills and deepening understanding of the material.